EFEITOS DO DÃ‰FICIT HÃDRICO SOBRE A CULTURA DO CAUPI (Vigna unguiculata (L.) WALP), CV. EMAPA-821. II- ANÃLISE DE CRESCIMENTO - Leite, Maysa de Lima; Rodrigues, JoÃ£o Domingos; Mischan, Marta Maria; Virgens Filho, Jorim Sousa das (REVISTA DE AGRICULTURA, 2015)
EFEITOS DO DÃ‰FICIT HÃDRICO SOBRE A CULTURA DO CAUPI (Vigna unguiculata (L.) WALP), CV. EMAPA-821. II- ANÃLISE DE CRESCIMENTO